Evaluation of a Hot Spot Policing Field Experiment in St. Louis, 2012 - 2014 - Rosenfeld, Richard ([Verlag nicht ermittelbar], 2017)
These data are part of NACJDs Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The two central objectives of this project were (1) to evaluate the effect on crime of a targeted patrol strategy mounted by the St. Louis Metropolitan Police Department (SLMPD) and (2) to evaluate the researcher-practitioner partnership that underlay the policing intervention. The study addressed the following research questions: Do intensified police patrols and enforcement in crime hot spots result in larger reductions in firearm assaults and robberies than in similar areas subject to routine police activity? Do specific enforcement tactics decrease certain type of crime? Which enforcement tactics are most effective? Does video surveillance reduce crime? How does the criminal justice system respond to firearm crime? Do notification meetings reduce recidivism? Does community unrest increase crime? Did crime rates rise following the Ferguson Killing? To answer these questions, researchers used a mixed methods data collection plan, including interviews with local law enforcement, surveillance camera footage, and conducting ride-alongs with officers.